2021
DOI: 10.1186/s12935-021-01952-6
|View full text |Cite
|
Sign up to set email alerts
|

RFX1: a promising therapeutic arsenal against cancer

Abstract: Regulatory factor X1 (RFX1) is an evolutionary conserved transcriptional factor that influences a wide range of cellular processes such as cell cycle, cell proliferation, differentiation, and apoptosis, by regulating a number of target genes that are involved in such processes. On a closer look, these target genes also play a key role in tumorigenesis and associated events. Such observations paved the way for further studies evaluating the role of RFX1 in cancer. These studies were indispensable due to the fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 162 publications
0
4
0
Order By: Relevance
“…Notably, this represented the major function of RFX1. Previous studies have described both the tumor-suppressive and oncogenic roles of RFX1, which involve the regulation of proliferation, the immune system, stemness, and chemoresistance 27 , 28 . To confirm that RFX1 is a binding target of miR-4508, a dual-luciferase assay was performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, this represented the major function of RFX1. Previous studies have described both the tumor-suppressive and oncogenic roles of RFX1, which involve the regulation of proliferation, the immune system, stemness, and chemoresistance 27 , 28 . To confirm that RFX1 is a binding target of miR-4508, a dual-luciferase assay was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Although RFX1 knockdown activated p38 MAPK and NF-κB signaling in fibroblasts, the links between RFX1 and p38 MAPK/NF-κB have not previously been established. RFX1 not only targets oncogenes (such as c-MYC ) but also downregulates some inflammation-related genes with pro-tumor activities (such as TGF-β2 , IL17A , and TLR4 ) 27 . Numerous studies have indicated that IL17A promotes the release of inflammatory factors and contributes to the development of pulmonary fibrosis 59 , 60 .…”
Section: Discussionmentioning
confidence: 99%
“…The binding of RFX and SOX family was most strongly impaired by PRDM6 expression in NES cells (Figure 4B). Notably, RFX transcription factors, including RFX1 16 , have been implicated in tumor suppression 17 , suggesting that reduced binding of these transcription factors in the presence of PRDM6 may have oncogenic potential in NES cells. Moreover, the binding of other transcription factors with roles in genome organization, development, and cell fate was affected ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our footprinting analysis shows significantly altered binding of transcription factors to open chromatin regions in PRDM6 NES cells. These include RFX1, a transcriptional repressor of tumor suppressors, and several other RFX transcription factors 16 . Notably, multiple RFX1 target genes, including the oncogene FGF1 , COL1A1 , and COL1A2 , are upregulated in PRDM6 NES cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, miR-3180-3p was reported to downregulate regulatory factor X1 (also referred to as RFX1 ), 49 which has both anticancer and cancer-promoting activities. 50 Indeed, it can regulate the expression of several proto-oncogenes as well as tumor suppressors, depending on tumor type and on spatial and temporal expression. 50 Thus, the interpretation of our results still needs more evidence about the role of this miRNA in cancer.…”
Section: Discussionmentioning
confidence: 99%